Effects of Business Education on Consumer Awareness and Conscious Consumption - Yilmaz, Mustafa Atahan; KoÃ§oÄŸlu, Duygu (European Scientific Journal, ESJ, 2017)
Consumer awareness and conscious consumption are well known concepts that gained higher value in time. Increased communication networks and tools let people to reach information sources about products and companies easier and faster. Consumer mind is affected by many other factors indeed. Education itself has pretty much effect on these concepts since it begins at very young ages and continues for many years. Most of the students have standard classes until the end of high school but when it comes to the college all of them have different professions according to their departments. While some of the departments are significantly related to the consumption and consumers, some of them are not even close to these topics. Business education is one of the departments in college which focus on consumer in all ways. These students gain different perspective and knowledge, become more informed consumers at the end of business education. This study aims to reveal effects of business education that comprises many consumption and consumer related classes as marketing, brand management, production management etc. on consumer awareness and conscious consumption. Two different student groups will be surveyed for this study. One of the groups consists of first grade students who are brand-new to business education and mostly have general classes. The other group consists of students who are last grade and succeed many consumption and consumer related classes. The data will be analyzed statistically and two groups of students will be compared. This study is important for revealing effects of business education knowledge on consumer awareness and consciousness.